Structure of the researcher competency of the teacher - Карпова, Л. Г. (Scientific notes of the pedagogical department, 2019)
A modern teacher, fulfilling the demands of the research paradigm of education, is obliged to constantly develop professionally, focusing on the educational needs of the student. Therefore, he must apply the methods of scientific knowledge in order to determine the individual characteristics of each student and on the basis of analysis of sources of scientific information, design, experiment, to develop the best teaching methods. At the same time, the requirements of the New Ukrainian School include the construction of an educational process based on the results of personal research. Therefore, the increased requirements for the implementation of the professional activities of the teacher of research require the development of his research competence.In the article, based on the analysis of scientific information, the structural components of the teacher's research competence, namely, motivational-value, cognitive, activity, personality and reflexive, are determined. On the basis of further study of psychological and pedagogical publications and personal experience of the author, each of them is described as follows. Motivational-value – defined as a system of motives and emotional-volitional attitudes of the teacher to the research activity; cognitive – is characterized as a system of methodological, psycho-pedagogical, interdisciplinary scientific knowledge of research activity; activity – specified through the possession of the skills to choose the appropriate goals and objectives of the implementation of information-analytical, model-design, experimental-measurement and evaluation and reflexive stages of research activities; personal – reflects the level of development of personality traits, which ensure the qualitative performance of research activities and reflexive – is defined as a system of skills for analysis, synthesis of research results and self-reflection.